PROSPECTS FOR THE INTRODUCTION OF ISLAMIC FINANCE IN UZBEKISTAN - Aliqoriev O.F. (American Journals, 2023)
This article discusses the financial operations performed by Islamic banks, the processes of working with customers, and their differences from traditional banks. Today, financial transactions in Islamic banks: deposit, credit, letter of credit, settlement, payment transactions are analyzed and scientific conclusions are formed.
Keywords: Shariah principles, Islamic banking system, financial intermediation, Muzoraba, Mudarib, Dual banking system.